Commercial banks performance 2008–2012 - Jasevičienė, Filomena; Povilaitis, Bronius; Vidzbelytė, Simona (Business, Management and Economics Engineering, 2013)
A country’s image, economic development process and GDP growth is significantly influenced by its banking sector performance. Banking’s success largely depends on public confidence. Only a small part of the banking services customers understand the indicators and ratios which are used to assess bank’s activities. Therefore, there is a need to analyze banks performance results in Lithuania. The paper presents a principal component analysis model applied on banks performance ratios in Lithuania. The main purpose of this article is to analyze basic indicators used in banks performance evaluation by principal component method. The obtained results represent the main components with the highest influence on Lithuanian commercial banks performance results in 2008–2012 year period. The main findings of the study indicate that commercial banks in Lithuania have been affected by different factors during 2008–2012 periods. It has been noted that Scandinavian capital commercial banks‘ performance results have been influenced by similar factors, have had similar structure of the factors, which has been more stable in comparison with small and/or Lithuanian capital banks. Conclusions and recommendations help banks’ board to improve their competitiveness and financial results, thus it also helps them to make appropriate decisions. It is also useful for an academic community to understand the structure of main components in banking sector.